The identification of a blood circular RNA signature that differentiates Chikungunya virus infection - Bai, Xue; Yan, Hanlin; Wen, Guoxia; Yuan, Shaoxun; Gu, Wanjun (Frontiers in Genetics, 2025)
ObjectiveChikungunya virus (CHIKV) is a re-emerging mosquito-borne human pathogen, which poses critical threats to the public health. However, an effective diagnostic method for early CHIKV infection remains scarce. Circular RNAs (CircRNAs) are a novel class of RNAs with important biological functions. They have been shown to be promising biomarkers for many human diseases. In this study, we sought to identify circRNA biomarkers in human peripheral whole blood for the early diagnosis of CHIKV infection.DesignCandidate circRNA biomarkers were identified by group comparison using a case-control study, which was further validated using an independent cohort. The performance of this signature and its correlation with clinical factors were estimated in both cohorts.ResultsUsing two public RNA-seq datasets of CHIKV infection, we developed and validated a 13-circRNA based blood signature that can discriminate CHIKV infectious patients from healthy controls. Furthermore, this blood circRNA signature was correlated with viral load in patients with CHIKV infection. Functional analysis implicated that these biomarker circRNAs were involved in the activation and regulation of immune processes against CHIKV infection.ConclusionCollectively, our findings indicated that peripheral blood circRNAs were potential biomarkers for the early diagnosis of CHIKV infection.